Geomorphology and stream habitat relationships with smallmouth bass abundance at multiple spatial scales in eastern Oklahoma - Dauwalter, Daniel C.; Splinter, Dale K.; Fisher, William L.; Marston, Richard A. (My University, 2007)
Fluvial geomorphic processes structure habitats important to stream fishes. We determined relationships between densities of smallmouth bass (Micropterus dolomieu) and ecoregions, watershed and reach morphology, and stream habitat in eastern Oklahoma, USA. Watershed and reach morphology were measured at 128 stream sites, and stream habitat and smallmouth bass abundance were measured in 1800 channel units. Variation in stream size, channel morphology, and substrate size constituted major physical differences among sites. Channel morphology differed among ecoregions in the largest streams. Densities of age-0 and age-1 and older smallmouth bass were approximately an order of magnitude greater in the Boston Mountains and Ozark Highlands streams than in Ouachita Mountains streams. Regression tree analysis explained less variation in age-0 (10-fold cross-validated relative error = 0.843) than in age-1 and older (relative error = 0.650) smallmouth bass densities and showed that stream size and channel-unit size were primary determinants of density. Channel morphology explained variation in densities in deep channel units of large streams, which was somewhat independent of ecoregion.
Keywords: Fluvial geomorphology; Fish habitat; Fish abundance; Boston Mountains; Ozark Mountains; Ouachita Mountains; Oklahoma